A Production and operations management study on Marton Manufacturing Philippines, Inc. - Fernandez, Glenn F. (College of Engineering, 2001)
A production and Operations Management study is conducted at Marton Manufacturing Philippines, Incorporated, with the main objective of assessing Marton's existing system regarding primarily the company's supply chain management, and other production management issues. After the assessment of which, recommendations are given so as to improve the ares of management that need changing for the better -- recommendations that befits the competitive priorities of Marton. This study, therefore, chiefly deals with the forecasting, aggregate planning, and inventory management system of the company--the central POM issues. Some other issues addresses that are related to these are the capacity utilization and the facility layout, both of which prove helpful in the valuation of the production and operations management of MArton. Naturally, the existing system is documented first, starting with the the details of the organization, then, with the production processes, and the, the supply chain management. In the course of the study, it is observed that Marton's operations management is lacking in some areas. First and foremost, the company do3s not do formal forecasting, thus production is reactive to orders placed by the customers, placing a great risk of having stockouts. Then, as the company does not do formal forecasting, it follows that they have no formal aggregate plans. The company could not have a formal inventory system either, which wilud have set the reorder points, ordering quantities, and the like, for a more secure system, all becaouse of the lack of forecasting. Aside from that, some other aspects of the production system of Marton, as mentioned, the capacity utilization and facility layout, add to the three major problems that the company faces. It could be seen, then, that the operations management problems of Marton are interrelated. And as the objective of the study is to be able to endorse systems that are suitable and parallel with Marton's competitive priorities, the group considered various forecasting techniques, evaluated each of them, and proposed the one that proved to be the most appropriate for Marton. This forecasting technique is the Weighted Moving Average, with n=3, weights=0.7,0.2,0.1, which is chosen in terms of the tracking signal that produced a negative value, which actually mean larger forecasts. This is deemed appropriate because the forecasts are larger than the actual sales, though the difference is kept at minimum, which agrees with the competitive priority of Marton--the on-time delivery. From that forecasting technique, the group came up with an aggregate plan that is supposed to effectively utilize the workforce of the company. What turned out to be the best is the same kind of strategy as of the existing one -- a level strategy. But this time, a different number of operators is set. From the current 52, the number is reduced to 34. This latter value is that which promised the least amount of total cost among the alternatives arrived at. As mentioned, having a forecasting system would allow Marton to have an inventory control system. Therefore, from the forecasting method arrived at, a set of inventory systems are presented as alternatives, from which, the Fixed-Order Quantity System is promising the total least cost per year -- a cost lower than the existing system. Aside from the cost, the alternatives are also set in such a way that they would offer service level that is consistent for each of the products, not like that of the existing system, which devotes service levels incongruent to the percentage of the demand for each product, thus giving the impression that the company uses up their capital in the most unsatisfactory way. From this inventory control system, reorder points are set for each of the raw materials, together with their reordering quantities. Aside from these three main problems, the group also addresses the issues with regards to facility layout and capacity utilization. Recommendations for the two areas are presented. And then, after the recommendations are given, an implementation strategy that can serve as guide for Marton is Presented.